PRICE BEHAVIOUR IN INDIA'S COCONUT SECTOR - DR. PRAFULLA K. DAS (CORD, 1991)
Coconut being a smallholder perennial crop, studies on the price behaviour of its products require serious consideration. A cursory look into the price structures of coconut, copra and coconut oil reveal that the price fluctuations are not only infrequent, but also most violent. The seasonal indices show different patterns for different products.